2021
DOI: 10.1158/1541-7786.mcr-20-0913
|View full text |Cite
|
Sign up to set email alerts
|

MAP3K7 Loss Drives Enhanced Androgen Signaling and Independently Confers Risk of Recurrence in Prostate Cancer with Joint Loss of CHD1

Abstract: Prostate cancer genomic subtypes that stratify aggressive disease and inform treatment decisions at the primary stage are currently limited. Previously, we functionally validated an aggressive subtype present in 15% of prostate cancer characterized by dual deletion of MAP3K7 and CHD1. Recent studies in the field have focused on deletion of CHD1 and its role in androgen receptor (AR) chromatin distribution and resistance to AR-targeted therapy; however, CHD1 is rarely lost without codeletion of MAP3K7. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…A putative mechanism of AR regulation by MAP kinases is direct phosphorylation, but a link between AR phosphorylation and MAP3K7 loss has not been identified [47,48]. Our previous study demonstrated that MAP3K7 loss, when co-lost with CHD1, is associated with increased AR activity [45]. Our meta-analysis supports these initial findings.…”
Section: Map3k7supporting
confidence: 81%
See 3 more Smart Citations
“…A putative mechanism of AR regulation by MAP kinases is direct phosphorylation, but a link between AR phosphorylation and MAP3K7 loss has not been identified [47,48]. Our previous study demonstrated that MAP3K7 loss, when co-lost with CHD1, is associated with increased AR activity [45]. Our meta-analysis supports these initial findings.…”
Section: Map3k7supporting
confidence: 81%
“…Recent studies have discovered that loss of CHD1 affects the distribution of AR chromatin binding. Many loci are differentially or newly bound by AR, resulting in more oncogenic expression profiles [45,52]. In concordance with its effects on AR chromatin distribution, patients with CHD1 loss exhibited higher than average AR scores, but not AR mRNA levels in our meta-analysis (Figure 2a,b).…”
Section: Chd1supporting
confidence: 70%
See 2 more Smart Citations
“…Biomarkers' "smart" manipulation was thought also to block the PCa recurrence after various types of treatments (e.g. [8,9].…”
Section: Introductionmentioning
confidence: 99%